Cyp2j5-Gene Deletion Affects on Acetylcholine and Adenosine-Induced Relaxation in Mice: Role of Angiotensin-II and CYP-Epoxygenase Inhibitor - Agba, Stephanie; Hanif, Ahmad; Edin, Matthew L.; Zeldin, Darryl C.; Nayeem, Mohammed A. (Frontiers in Pharmacology, 2020)
Previously, we showed vascular endothelial overexpression of human-CYP2J2 enhances coronary reactive hyperemia in Tie2-CYP2J2 Tr mice, but we did not see the response in CYP2J-epoxygenase knockout mice. Therefore, we hypothesized that Cyp2j5-gene deletion affects acetylcholine-, NECA (adenosine)-and CGS 21680 (adenosine A2A receptor)-induced relaxation and their response is partially inhibited by angiotensin-II (Ang-II) and ω-hydroxylase inhibitor in mice. ACh-induced response was tested with N-(methylsulfonyl)-2-(2-propynyloxy)-benzenehexanamide (MS-PPOH, CYP-epoxygenase inhibitor; 10-5M) and Ang-II (10-6M). In Cyp2j5-/- mice, ACh-induced relaxation was different from C57Bl/6 mice, at 10-5 M (76.1 ± 3.3 vs. 58.3 ± 5.2, P<0.05). However, ACh-induced relaxation was not blocked by MS-PPOH in Cyp2j5−/−: 58.5 ± 5.0%, P>0.05, but blocked in C57Bl/6: 52.3 ± 7.5%, P<0.05, and Ang-II reduces ACh-induced relaxation in both Cyp2j5-/- and C57Bl/6 mice (38.8 ± 3.9% and 45.9 ± 7.8, P <0.05). In addition, NECA-induced response tested with Ang-II and 20-HETE inhibitor, dibromo-dodecenyl-methylsulfimide (DDMS, 10-5M). In Cyp2j5-/- mice, NECA-induced response was not different from C57Bl/6 mice at 10-5M (23.1 ± 2.1 vs. 21.1 ± 3.8, P>0.05). However, NECA-induced response was reduced by Ang-II in both Cyp2j5-/- and C57Bl/6 mice (-10.8 ± 2.3% and 3.2 ± 2.7, P <0.05), and the reduced response due to Ang-II was partially rescued by DDMS in both Cyp2j5-/- and C57Bl/6 mice (at 10-5M, A2AAR-agonist, CGS-21680, 15.8 ± 3.4% and 13.0 ± 2.3, P <0.05). Data suggest that ACh-induced relaxation in Cyp2j5-/- mice depends on nitric oxide (NO) but not CYP-epoxygenases, and the NECA-induced different response in male vs. female Cyp2j5-/- mice when Ang-II treated.